The Influence of Company Size, Profitability, and Leverage on the Quality of Financial Reports (Study on Cigarette Companies Listed on the IDX for the Period 2018-2023) - Ayu Apriliani (Citakonsultindo, 2024)
The purpose of this study is to examine the influence of company size, profitability, and leverage on the quality of financial statements of cigarette companies listed on the Indonesia Stock Exchange in 2018-2023. This study uses secondary data in the form of annual financial statements published by cigarette companies in 2018-2023 which can be accessed through the official website of the Indonesia Stock Exchange. The sample was determined using purposive sampling using five cigarette companies listed on the Indonesia Stock Exchange. Furthermore, data processing uses the SPSS 10 application. Based on the results of the study, all independent variables (company size, profitability, and leverage) simultaneously have a positive effect on the quality of financial statements. Meanwhile, partially, profitability and leverage have no effect on the quality of financial statements. Only the variable of company size affects the quality of financial statements.